Bromide Induced Room‐Temperature Formation of Photoactive Formamidinium‐Based Perovskite for High‐Efficiency, Low‐Cost Solar Cells (Solar RRL 4∕2019). Issue 4 (8th April 2019) - Lv, Xinding; Dong, Xuemei; Ye, Zhili; Zhou, Junshuai; Deng, Fei; Zheng, Yan‐Zhen; Tao, Xia
Abstract : In article no.1800313, Yan‐Zhen Zheng, Xia Tao, and co‐workers report bromide‐induced room temperature crystallization of highly photoactive black phase formamidinium‐based perovskite films with high performance and reproducibility.